Porthmion Archaeological Expedition of the Institute for History of Material Culture, RAS – Institute of Archaeology, NASU - Vakhtina, Marina Ju. (Hyperboreus, 2015)
A survey of the excavations at Porthmion conducted by the archaeological expedition of IIMK, Russian Academy of Sciences, and the Institute of Archaeology of the National Academy of Sciences of Ukraine.